Pemberdayaan Masyarakat Berbasis Lingkungan Melalui Program Kuliah Kerja Nyata di Desa Buni Bakti, Kecamatan Babelan, Kabupaten Bekasi - Rendy Rusdiyanto; Azahwa Syalwa Syafirasunar; Dhiandra Namira Invionita; Nuna Lailani; Revanya Adinda Putri; Ikhsan Darmawan; Aqil Malik Albaihaqi; Amalia Maharani; Robani Satria Perwira Hariyadi; Setia Mandala; Angelika Pramudita; Lulu Ilmaknun Al Zahra; Laser Romeo Hutasoit; Cris Kuntadi (Yayasan Daarul Huda Kruengmane, 2026)
The Community Service Learning (KKN) activity of Group 66, Universitas Bhayangkara Jakarta Raya, was conducted in Buni Bakti Village, Babelan District, Bekasi Regency for 30 days during May–June 2026. Preliminary observations identified key issues including low public awareness of waste management, insufficient green space, and limited understanding among children regarding positive behavior and discipline. Three work programs were designed: (1) Waste Bank Socialization and Community Cleanup attended by residents of RT 09, (2) Children's Environmental Education involving 25 elementary school-aged children, and (3) Greening and Waste Decomposition Education through seedling planting and installation of educational boards. A participatory and educational approach was applied, actively engaging Buni Bakti Village residents. Results showed the establishment of a waste bank unit, expansion of green zones in the village, and improved awareness and understanding among children regarding environmental stewardship and positive conduct. This KKN program contributed to strengthening village community capacity through sustained knowledge transfer and direct practice.